THE INFLUENCE OF SOCIAL MEDIA AND SALES PROMOTION ON IMPULSIVE BUYING BEHAVIOR ON SHOPEE E-COMMERCE ON STUDENT AT FACULTY OF ECONOMICS AND BUSINESS SAM RATULANGI UNIVERSITY MANADO - Trifena Monica Derek; Sifrid S. Pangemanan; Maria V. J. Tielung (Universitas Sam Ratulangi, 2022)
Abstract: Impulsive buying behavior seems to be a contradiction between what individuals planned and what individuals do. Impulsive buying behavior, on the consumer side, has negative consequences, such as excessive spending on money, useless buying, lasting uncertainties and risks in terms of product function and quality, and a sense of guilt. Impulsive buying, therefore, often deemed irrational and risky.The objective of this research was to analyze the influence of social media and sales promotion toward impulsive buying behavior on Shopee e-commerce among the students at Faculty of Economics and Business Sam Ratulangi University Manado. The research approach of this study was quantitative method. Multiple linear regression was used to analyze the relationship of each variable. The data collected using questionnaire with 100 respondents as the sample. The result of this research showed that social media and sales promotion partially has positive and significant influence on impulsive buying behavior.Keywords: Social Media, Sales Promotion, Impulsive Buying Behavior.